2019
DOI: 10.1108/bl-05-2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of consumer information acquisition confidence, social outcome confidence on information search and sharing

Abstract: Purpose This study aims to highlight the impact of information acquisition confidence and social outcome confidence on information search and information share intention. Moreover, the role of subjective knowledge is analyzed as a mediating variable among these relations. Design/methodology/approach This study conducted a survey which generated 233 valid responses. The data were analyzed using component factor analysis and structural equation modeling. Whereas, to examine the mediating effect, Hayes and Prea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 75 publications
4
9
0
Order By: Relevance
“…As a result, consumers of high subjective knowledge tend to search and share more information because this information signifies the level of consumer confidence (Park and Lessing, 1981). Therefore, these findings align with studies of Zubair et al (2019); Utkarsh et al (2018) and Bearden et al (2001).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As a result, consumers of high subjective knowledge tend to search and share more information because this information signifies the level of consumer confidence (Park and Lessing, 1981). Therefore, these findings align with studies of Zubair et al (2019); Utkarsh et al (2018) and Bearden et al (2001).…”
Section: Discussionsupporting
confidence: 88%
“…Still, the information sharing behavior and its relationship with subjective knowledge are not much highlighted by studies (Yuan et al, 2016). Zubair et al (2019) highlighted that there is a significant relationship between social outcome confidence and subjective knowledge. Moreover, subjective knowledge positively influences the information searching and sharing intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research has mainly focused on investigating the impact of knowledge sources on frugal innovation. Future studies can use information credibility, environmental dynamism or environmental capabilities as moderating variables (Zubair et al, 2019;Erkan and Evans, 2016).…”
Section: Limitations and Future Recommendationsmentioning
confidence: 99%
“…It is believed that the social environment provides a clue to a person in constructing or interpreting events and situations. Zubair et al (2019) found the positive influence of social outcome toward the individual's subjective knowledge and behavior intention. Particularly in mobile users, it is stated, "mobile users are often in social situations and it influences their perceived usefulness and perceived ease of use when they find other societal group members using mobile application" (Sathye et al, 2016, p. 3).…”
Section: Literature Reviewmentioning
confidence: 90%